2000
DOI: 10.1159/000012087
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Prognostic and Survival Factors Related to Treatment of Low-Grade Astrocytomas in Adults

Abstract: Prognostic factors for low-grade astrocytomas have been proposed, but optimal treatment remains controversial. Eighty-eight consecutive adult patients with supratentorial low-grade astrocytomas were retrospectively reviewed to determine specific factors influencing outcome. All underwent craniotomy (43 radical resections, 45 nonradical resections). Sex, age at diagnosis, preoperative Karnofsky performance status (KPS), tumor location, estimated extent of resection, radiation, chemotherapy, histological type, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
2
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(58 citation statements)
references
References 27 publications
0
51
2
5
Order By: Relevance
“…19,50,55,59 In the literature, 5-year survival ranges from 42% to 98%. 16,31,32,35,38,42,43,58,61 To date, there is still no general consensus regarding the effect of EOR on OS among patients with LGGs, due to the lack of Class I evidence. However, since 1990, many different studies have been published evaluating the benefit of the maximum EOR of glioma in improving OS and delaying tumor progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,50,55,59 In the literature, 5-year survival ranges from 42% to 98%. 16,31,32,35,38,42,43,58,61 To date, there is still no general consensus regarding the effect of EOR on OS among patients with LGGs, due to the lack of Class I evidence. However, since 1990, many different studies have been published evaluating the benefit of the maximum EOR of glioma in improving OS and delaying tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies since 1990 have provided a subjective analysis, based on the surgeon's intraoperative impression, rather than a statistical analysis to examine the efficacy of EOR in improving patient survival and delaying tumor progression. 1,2,15,16,27,32,35,36,38,39,42,43,49,52,54,58,60,61 Only 5 studies have included a volumetric analysis of EOR, multivariate, and univariate analyses, to determine the statistical significance of EOR. 16,49,52,54,58 Of these, the largest analysis with volumetric quantification of EOR demonstrated a major effect of EOR on OS for hemispheric LGGs.…”
mentioning
confidence: 99%
“…4 46 Low-grade gliomas carry a better prognosis, although the vast majority of patients eventually die of their disease and 5-year survival percentages range from 42 to 92% in the literature. 51,52,59,76,84,96,97,123 For all gliomas, the identification of universally applicable prognostic factors and treatment options remains a great challenge. Among the many tumor-and treatmentrelated parameters, only patient age and tumor histological characteristics have been identified as reliable predictors of patient prognosis, although tumor location in an eloquent area and a patient's functional status can also be statistically significant.…”
Section: Assessing the Value Of Glioma Extent Of Resectionmentioning
confidence: 99%
“…However, such an association has not been established in adult or pediatric low-grade gliomas. Nakamura et al 48 reported that in adults with low-grade gliomas, neither p53 nor MIB-1 staining was associated with prognosis. Similarly, Machen et al 49 reported that MIB-1 staining in 48 pilocytic astrocytomas was negative in 66.7% of patients and that outcome was not correlated with MIB-1.…”
mentioning
confidence: 99%